(untitled) (Research, Society and Development, 2026)
The overall objective of this work is to identify the impacts of using cell salvage in cardiac surgery to reduce allogeneic blood transfusions, aiming to decrease postoperative complications and reduce costs. To this end, the following specific objectives were defined: contextualizing blood transfusion in the intra- and postoperative periods; the use of cell salvage in cardiac surgery; and identifying the main impacts of using this technology, focusing on the reduction of postoperative complications. Addressing the use of cell salvage in cardiac surgery is justified by the relevance and high complexity of cardiac surgical procedures. This technique has proven to be an effective strategy to increase patient safety and contribute to better clinical outcomes. This study consists of descriptive, qualitative research, structured from an integrative literature review, using the following keywords: cell salvage, cardiac surgery, and postoperative cardiac care, performed in the PubMed database, from 2015 to 2025. Through the collection of information throughout the research and the analysis of the data, it was possible to conclude that the use of cell salvage is associated with a reduction in the need for allogeneic blood transfusions, better maintenance of hemoglobin levels, and attenuation of the systemic inflammatory response, provided it is used appropriately. Further studies, especially in the national context, are needed for a better evaluation of its cost-benefit ratio.